Approval Drawing in EPC Fidic and its Implications on Contractual Injuries - Irpan Logitra Purba; Sami’an Sami’an; Sarwono Hardjomuljadi (Interdisciplinary Social Studies, 2025)
This research analyzes contractual challenges arising from the Owner's involvement in engineering drawing approvals within Engineering, Procurement, and Construction (EPC) contracts, using the 500 kV Sumatra Transmission Project as a case study. Under the FIDIC Silver Book, the contractor bears full responsibility for engineering, procurement, and construction; however, PT PLN (Persero)'s review and approval of drawings introduced legal ambiguity and contributed to delays that led to Extension of Time (EOT) claims. Using a normative legal research method, the study shows that delays caused by Owner-initiated revisions constitute a valid basis for EOT under Sub-Clause 8.4, provided claims are submitted timely and supported by evidence. Conversely, procedural non-compliance may classify such delays as contractor default, subjecting the contractor to liquidated damages. The research concludes that Indonesia's civil law framework has not fully integrated FIDIC Silver Book principles, particularly regarding EOT processes, risk allocation, and dispute resolution. The study recommends standardizing EPC governance and clarifying Owner involvement.